Perception Of Witchcraft Practice In Oredo Local Government Area Of Edo State, Nigeria - Nwatu, Uche Louisa; Ebue, Malachy Okechukwu; Iwuagwu, Anthony Obinna; Ene, Jacinta Chibuzor; Odo, Casmir Obinna (Advances in Social Sciences Research Journal, 2021)
Africa has long standing history of complex phenomenal as they relate to belief system, especially in the existence and powers of witches which pervades every segment of the society. This study is designed to ascertain the perception of witchcraft practice in Oredo Local Government Area of Edo state, Nigeria. The study used a cluster/multi stage random sample of 30 residents of Oredo Local Government Area whom were interviewed using FGDs and in-depth interviews to elicit information on the perception and practice of witchcraft in Edo state, Nigeria. Data generated were content analyzed and the result shows that majority of the respondent were of the opinion that witchcraft is widely practiced in Edo state and it has negative implications to victims. They emphasized its human right implications, noting that it could result in total violation of rights. Results further show that witchcraft accusation is gender biased as women (elderly) are mostly the victims of witchcraft accusation against their male counterparts, thereby raising concerns on gender based discrimination as well as human right violation respectively. It becomes highly imperative that social workers and other human rights professionals should raise awareness on the existence of these problems and carryout necessary advocacy, influencing the government to enact and enforce stronger laws and strategies to address all aspects of this issue.